Myofibrillar structural changes caused by marination with calcium phosphate or calcium chloride and sodium pyrophosphate - Lawrence, T.E.; Waylan, A.T.; Kastner, Curtis L. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Ultrastructural changes were studied in beef eye of round muscle after 120 hours marination in 0.5, 0.75, or 1.0% calcium phosphate (CaPO) or 2, 4, or 6% calcium chloride or 1% sodium pyrophosphate (CaCl+NaPO) solutions. Increasing the concentration of CaPO caused decreasing myofibril width and increasing myofilament degradation. Increasing the concentration of CaCl+NaPO caused increasing loss of I-band material. Marination of beef eye of round muscle in calcium phosphate or calcium chloride + sodium pyrophosphate solutions caused denaturation of myofibrillar proteins likely due to marinating solution acidity.
Keywords: Beef; Marinades; Muscle structure